Detection of limited-energy α particles using CR-39 in laser-induced p −11B reaction - Wang, Putong; Deng, Xiangai; Ma, Zhiguo; Fu, Changbo; Fan, Lulin; Wang, Qingsong; Xu, Jiancai; Xu, Tongjun; Ji, Liangliang; Shen, Baifei; Liu, Yancheng; Cao, Xiguang; et al. (Frontiers in Physics, 2023)
Due to the harsh radiation environment produced by strong laser plasma, most of the detectors based on semiconductors cannot perform well. So, it is important to develop new detecting techniques with higher detection thresholds and highly charged particle resolution for investigating nuclear fusion reactions in laser-plasma environments. The Columbia Resin No. 39 (CR-39) detector is mainly sensitive to ions and insensitive to the backgrounds, such as electrons and photons. The detector has been widely used to detect charged particles in laser-plasma environments. In this work, we used a potassium–ethanol–water (PEW) etching solution to reduce the proton sensitivity of CR-39, by raising the detection threshold for the research of laser-induced 11B(p, α)2α reaction. We calibrated the 3–5 MeV α particles in an etching condition of 60°C PEW-25 solution (17% KOH + 25%C2H5OH + 58%H2O) and compared them with the manufacturer’s recommended etching conditions of 6.25 N NaOH aqueous solution at 98°C in our laser-induced nuclear reaction experiment. The results indicate, with the PEW-25 solution, that CR-39 is more suitable to distinguish α tracks from the proton background in our experiment. We also present a method to estimate the minimum detection range of α energy on specific etching conditions in our experiment.